3D Printing of Anisotropic Multimaterial Structures using Acoustic Streaming-assisted Two-Photon Polymerization. (September 2022) - Lichade, Ketki M.; Pan, Yayue
Abstract: Recently, many studies have investigated anisotropic multimaterial structures for their potential in various applications, thanks to their tunable anisotropic physical properties. A significant challenge in these product innovations is the limited choices of manufacturing technologies for fabricating the desired anisotropic multimaterial structures with precise topological and chemical composition control. This study reports a new manufacturing method, Acoustic-Streaming-assisted Two-Photon Polymerization (AS-TPP), for fabricating anisotropic multimaterial structures through integrating layer-by-layer printing and acoustic-streaming-assisted particle patterning at a nano- and micro- scale. To study the effectiveness of this method, a set of structures with different topology and material compositions is fabricated using the conventional TPP technique and this novel AS-TPP technique. The scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDS) analysis of the fabricated samples validated the accuracy of the AS-TPP process in the geometry and material composition control. Experimental results validated the manufacturing capability of the novel AS-TPP process in terms of material patterning, surface structuring, and anisotropy production. To demonstrate possible applications, the anisotropic wettability and water collection capability of the printed samples were measured and compared. The water collection efficiency of the anisotropic multimaterial structure with groove surface fabricated by AS-TPP was three times higher than that of the isotropic single-material structure with flat smooth surface. This work implied the great potential of the AS-TPP technique for the productions of materials or devices with advanced shape and material designs for various applications such as microfluidics, optics, functional surface coating, cell screening, and biomedical devices.